Penerapan Teknik Self Management Untuk Meningkatkan Kontrol Diri Pecandu Narkoba (Studi Kasus Pada Klien “Y” Di Yayasan Pusat Rehabilitas Narkoba Ar Rahman Palembang) - Ayu, Putri; Razzaq, Abdur; Noviza, Neni (Jurnal Ilmu Sosial, Humaniora dan Seni, 2022)
This research is entitled "Application of Self Management Techniques to Improve Self Control of Drug Addicts (Case Study on Client "Y" at the Ar Rahman Drug Rehabilitation Center Foundation Palembang. The purpose of this research is to find out the description of the client's self-control "Y" and to find out how the application of self management techniques to improve self-control for client "Y". This type of research is field research using a qualitative approach and case study method. Data collection tools in this study are observation, interviews and documents. The data analysis methods in this study are pattern matching, data annotation, and time series analysis. The subjects of this research are client "Y" and the counselor of client "Y". The results of this study that the description of self-control in client "Y" includes four aspects of the first angry emotion including facial features, tongue features, limb features, and heart features. And this description of self-control can also be seen from three aspects of self-control, namely: behavior control, namely client "Y" is sometimes unable to regulate his behavior, especially in his emotional control, cognitive control (cognitive control) in cognitive control is quite good, it's just hard to control his emotions, client "Y" is sometimes a little difficult to get information well, and finally control satisfaction (decisional control) in controlling satisfaction is quite good, client "Y" is quite aware of how to control satisfaction from himself. not good, because it is still difficult to control his emotions. The steps in applying self management techniques are the first stage of self-monitoring or self-observation, the counselor knows that client "Y" has observed his own behavior. In the second stage of the self-assessment process, the counselor observes the client comparing behaviors. The third stage is eradication or punishment (self-reinforcing), the client has never punished himself. And then the last stage of target behavior, the client has assessed changes in his own behavior. The result of the application of self management techniques is that client "Y" in his self-control is getting better, client "Y" is now able to control his emotions.